HOAXES IN THE PERSPECTIVE OF THE QURAN: EFFORTS AND CHALLENGES TO PREVENT HOAXES IN THE ERA OF SOCIETY 5.0 - Astuti, Ruli; Hamidah , Tutik; Nisak, Nur Maslikhatun (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article discusses hoax in the perspective of the Qur'an, attempts to mitigate hoax from the Islamic perspective, the importance of digital literacy to overcome the spread of hoax and the challenges in dealing with the spreading of hoax in the era 5.0. This study used literature review to gather and analyze research findings. The researcher collected various sources such as articles, journals, and previous research result. This study found that the spread of hoax can cause a variety of problems, such as triggering conflict between religious groups, and destroying the unity of nations. Some steps can be taken to prevent hoax, including by checking the truth of information, tawaqquf, and improving the culture of literacy. The main challenge of preventing hoax in the society 5.0 era is the low literacy of society. Other challenges include the lack of preparedness of various parties to deal with the spread of hoax, as well as many hoax spreaders using fake accounts